Aplicações de calcário e silicato no desenvolvimento de alface sob estresse causado por nematoide das galhas - Oliveira, Daiane de Deus (2021)
Lettuce is one of the main vegetables, as well as one of the most consumed worldwide. Its production basically consists of field, glasshouse, or greenhouse, considering that in the latter it is possible to control temperature, light, and humidity. The main nutritional recommendation is via nitrogen, phosphorus, and potassium fertilization. However, soil pH corrections are required via limestone application. Its production can be severely reduced, due to pests and phytosanitary diseases; among these, the parasitoid phytomatomatids of the plant’s root system stand out, being responsible for dwarfism and yellowing of the cultivars, caused by the respective lack of absorption of water and nutrients by the roots. One of the forms of control proposed in this work are applications of four dolomitic limestone treatments (0; 1.41; 2.83; 4.25 g) and calcium and magnesium silicate (0; 0.425;0.850; 1.28 g) with twelve retentions, thus adding up to 48 units in each experiment, in a completely randomized design, in five-liter pots in an oven, 180 days before transplanting the lettuce seedlings. That occurs because calcium is the main component of the cell walls of plants, as well as being responsible for some of these physiological processes. Silicon is a nutrient considered non-essential for plants; however, it helps in the formation of the endoplasmic smooth and rough reticulum and the Golgi complex, acting as a drain to remove sugars originated in the chloroplasts into other parts of the plants, thus reducing its attractiveness to pests and diseases. Silicon is also responsible for the formation of a layer above the epidermis, making the cell wall tougher. Through this, 1000 eggs of Meloidogyne javanica nematodes were inoculated in Regina lettuce cultivars for a period of 60 days, so that two complete cycles of phytonmatoids could take place. Thus, height, fresh and dry matter content of plants were assessed, as well as the content of carotenoids and chlorophyll by spectrophotometry and NDVI, in which it was also possible to calculate the water and photochemical reflectance. At the end, the correlation between the different methods of chlorophyll readings was verified. Manual counting of the number of galls was carried out, as well as counting the number of eggs per root under a microscope and number of eggs in the soil. The data were submitted to analysis of variance using the F Test (p <0.05) and the averages were compared using the Tukey test at 5% probability. Regression analysis was performed for the results, determining the regression equations. None of the results found differed statistically; however, calcium treatments showed better responses to nematode control than silicate treatments, as well as for the evaluated parameters. The content of chlorophyll and carotenoids, height, fresh and dry pasta, may have been affected by the stress suffered by the plants at the root. It is concluded that the treatments with limestone and silicate were not efficient for the control of M. javanica, in addition to not providing an increase in the other parameters evaluated.